LEGAL ANALYSIS OF THE RESOLUTION OF THE PEACE AGREEMENT IN THE PKPU AND BANKRUPTCY CASE OF SRITEX - Heru Herdian Herawan (CV. RADJA PUBLIKA, 2025)
PT Sri Rejeki Isman Tbk (Sritex) entered a suspension of debt payment obligations (PKPU) in May 2021 with liabilities of approximately IDR 12.9 trillion and obtained a court-approved settlement (homologation) in January 2022. However, the company failed to fulfill its post-homologation obligations, leading the Semarang Commercial Court to revoke the homologation and declare Sritex bankrupt in October 2024, a decision that subsequently became final and binding after the Supreme Court rejected the cassation appeal. The bankruptcy affected the administration of assets by the curator, the rights of creditors and subsidiaries, and raised legal issues concerning the validity of the homologation revocation, the protection of the parties, and the application of the principles of good faith and proportionality. The objectives of this research are, first, to examine the legal consequences of the revocation of the settlement agreement in the PKPU and bankruptcy proceedings of PT Sri Rejeki Isman Tbk (Sritex); and second, to analyze and determine the legal implications of Decision No. 12/Pdt.Sus.PKPU/2021/PN.Smg in conjunction with Supreme Court Decision No. 556 K/Pdt.Sus-Pailit/2024, Decision No. 2/Pdt.Sus-Homologasi/2024/PN Niaga Smg in conjunction with Supreme Court Decision No. 1345 K/Pdt.Sus-Pailit/2024, for Sritex’s creditors. This study employs normative legal research. The findings indicate that the revocation of a settlement agreement (homologation) within the PKPU and bankruptcy mechanism constitutes a legal instrument to protect creditors when the debtor fails to perform its obligations, as regulated under Law Number 37 of 2004, which allows the debtor to be directly declared bankrupt. In the case of PT Sri Rejeki Isman Tbk (Sritex), the revocation of homologation signifies a shift from debt restructuring to bankruptcy in the collective interest of creditors, in line with Thomas H. Jackson’s Creditor Protection Theory and John Rawls’s principles of justice and proportionality. From the perspective of law and economics and the values of Pancasila, this measure functions as a corrective mechanism to prevent inefficiency and uncertainty, while ensuring a fair, proportionate, and sustainable distribution of assets in accordance with the 1945 Constitution of the Republic of Indonesia.